2021
DOI: 10.1186/s12966-021-01097-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the correlates of outdoor play and time among children aged 3-12 years

Abstract: Background Due to the myriad of benefits of children’s outdoor play and time, there is increasing concern over its decline. This systematic review synthesized evidence on the correlates of outdoor play and outdoor time among children aged 3-12 years. Methods A total of 12 electronic databases in five different languages (Chinese, English, Korean, Spanish, Portuguese) were searched between October 28, 2019 and July 27, 2020. Covidence software was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 144 publications
(607 reference statements)
7
73
2
3
Order By: Relevance
“…Whereas parental support was moderately related to PA engagement, perceived peer support was loosely associated with PA. During childhood, parental support seems to impact motor development and PA, which is in agreement with our findings involving 8–12-year-old children, whereas as children transit into adolescence, the impact of peer support gains relevance [ 30 , 58 ], i.e., parents seem to be the primary socializing agents for children’s PA engagement formation throughout childhood and thus, represent a key factor to target [ 70 ]. A recent systematic review has shown that parents’ support is an effective correlate for PA engagement in terms of co-participation, family involvement, emotional, informational, companionship, and instrumental [ 58 ], which supports the notions of the bioecological theory [ 26 ]. Bronfrenbrenner [ 26 , 68 ] postulated the existence of different systems to understand human development by interrelated ecological levels (i.e., microsystem, mesosystem, exosystem, and macrosystem).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Whereas parental support was moderately related to PA engagement, perceived peer support was loosely associated with PA. During childhood, parental support seems to impact motor development and PA, which is in agreement with our findings involving 8–12-year-old children, whereas as children transit into adolescence, the impact of peer support gains relevance [ 30 , 58 ], i.e., parents seem to be the primary socializing agents for children’s PA engagement formation throughout childhood and thus, represent a key factor to target [ 70 ]. A recent systematic review has shown that parents’ support is an effective correlate for PA engagement in terms of co-participation, family involvement, emotional, informational, companionship, and instrumental [ 58 ], which supports the notions of the bioecological theory [ 26 ]. Bronfrenbrenner [ 26 , 68 ] postulated the existence of different systems to understand human development by interrelated ecological levels (i.e., microsystem, mesosystem, exosystem, and macrosystem).…”
Section: Discussionsupporting
confidence: 88%
“…In the social environment, there are multiple reasons associated with the downward general trend in children’s PA (e.g., parental concerns, changing social norms around children’s independent mobility, an increase in sedentary leisure activities, and/or screen time, etc. ), which limit children’s PA engagement [ 58 ]. It is thus important to recognize the underlying social mechanisms that explain children’s PA to understand their movement behavior and/or to prepare interventions focused on children’s health [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies investigated associations between habitual physical activity, sedentary behavior, and outdoor play. A recent systematic review about correlates of outdoor play in children between three and 12 years supported positive associations between outdoor play and physical activity, while there was largely no relationship observed between screen time or screen exposure as a proxy for sedentary behavior and outdoor play [18]. Again, most of the studies were cross-sectional and most of the studies looked at children in preschool age [18].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review about correlates of outdoor play in children between three and 12 years supported positive associations between outdoor play and physical activity, while there was largely no relationship observed between screen time or screen exposure as a proxy for sedentary behavior and outdoor play [18]. Again, most of the studies were cross-sectional and most of the studies looked at children in preschool age [18]. Fewer studies investigated associations between habitual outdoor play, moderate-to-vigorous physical activity, and sedentary behavior in older children: In 11year-old children, high levels of outdoor play were associated with more moderate-to-vigorous physical activity and less sedentary behavior on weekend days for boys and girls, while on weekdays, these associations were only observed for boys [19].…”
Section: Introductionmentioning
confidence: 99%